Physware: A Collaborative Initiative for Strengthening Physics Education and Promoting Active Learning in the Developing World - Jolly, Pratibha (Scientia in educatione, 2017)
Project Physware emanates from globally shared concerns on the lack of high-quality education in physics with detrimental consequences on scientiﬁc research and socio-economic progress. A signiﬁcant milestone in international cooperation, Physware aims to provide a sustainable collaborative model for capacity building of physics educators through a series of Educate the Educator workshops for those in the developing countries. The workshops are carefully designed to promote activity based pedagogic methods proven to be eﬀective through rigorous educational research. They propagate curriculum and resource materials that are easily adapted to the needs of any region. While the emphasis is on using lowcost equipment and appropriate technologies that are locally accessible, participants are also introduced to ways of integrating emerging computer-based technologies for physics teaching, contemporary research, and applications of relevance to the work place. They explore ways of teaching fundamental new physics within the context of contemporary pedagogy that is both, hands-on and minds-on. After the success of a pilot workshop held at Trieste in 2009, the Physware series was launched in 2012 from the University of Delhi. Both workshops brought together a vibrant and eclectic group of participants who contributed actively to creation of innovative resource materials. It is hoped that many participants will emerge as regional leaders. Feedback shows that going beyond the constraints of its workshop format, Physware has the potential to emerge as a professionally networked community of practice.